2020
DOI: 10.1186/s42269-020-00407-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimum conditions of killer toxins produced by Torulaspora delbrueckii and Wickerhamomyces anomalus and their action as antifungal agents

Abstract: Background This study was conducted to estimate the antifungal activity and efficiency of purified killer toxins (TK and WK) produced by Torulaspora delbrueckii and Wickerhamomyces anomalus as alternative drugs of resistant strains against several pathogenic fungi (Candida albicans, Aspergillus niger, and Aspergillus flavus). A specific focus was on the antifungal activity of such purified proteins by using a simple and economical tools under controlled conditions of fermentations. Results The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…While we limited ourselves to specific screening conditions, which miss antifungal yeasts that target pathogens not represented in our panel or that require specific conditions for activity (e.g. high salt concentration, 107,108 a specific pH [77][78][79][80][81][82] or temperature [79][80][81][82] or a transcriptional activator 109 ), our workflow can be adapted to other pathogens and screening conditions that a future researcher is interested in. Specific growth or selection conditions required for continuous production of a killer toxin could explain why some of our killer yeast candidates lost the inhibitory activity along our study.…”
Section: Assessment Of the Workflowmentioning
confidence: 99%
See 2 more Smart Citations
“…While we limited ourselves to specific screening conditions, which miss antifungal yeasts that target pathogens not represented in our panel or that require specific conditions for activity (e.g. high salt concentration, 107,108 a specific pH [77][78][79][80][81][82] or temperature [79][80][81][82] or a transcriptional activator 109 ), our workflow can be adapted to other pathogens and screening conditions that a future researcher is interested in. Specific growth or selection conditions required for continuous production of a killer toxin could explain why some of our killer yeast candidates lost the inhibitory activity along our study.…”
Section: Assessment Of the Workflowmentioning
confidence: 99%
“…Activity was judged by a growth inhibition halo around the isolate (Figure 3A) to better visualize the presence of a growth inhibition halo. As most yeast killer toxins showed optimal fungicidal activity at acidic pH and ambient temperature [77][78][79][80][81][82] , we performed this first screening assay at pH 4.0 and 25 °C.…”
Section: % Of the Yeast Isolates Show Antifungal Activity With A Vari...mentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic studies in Saccharomyces cerevisiae have shown that the ability to produce killer toxins is cytoplasmically inherited and related to the presence of double-stranded linear RNA (dsRNA) plasmids, which are then encapsulated, forming non-infectious virus-like particles (VLP) within the cell cytoplasm [66]. All killer toxins are produced under acidic conditions, and their activity decrease with the increase in pH and temperature of the medium in which they are found-an increase in these variables is sufficient for the yeasts to stop producing them [67,68].…”
Section: Killer Toxinmentioning
confidence: 99%